An investigation to technical efficiency, and its relationship with stock price: Evidence from South Korea and Singapore listed banks - YU, FANG (2014)
Abstract: Because the liberalization of global financial system, banks are operating in an increasing competitive business conditions, which pushed banks putting more efforts in generating benefits for their shareholders. Thus, the performance of banks and its relationship with stock price have become one of the most important topics in banking industry. This dissertation will extend the literature on banks’ efficiency and its relationship with stock price. Moreover, in order to fill the gap of most empirical studies, this paper will also test risk factors. Therefore, Z score is introduced and is examined in relationship with stock price. However, the results show that there is no relationship between banks’ efficiency and stock price, and Z score is also not related with stock price.